Actual aspects of chronic cystitis pharmacotherapy in women in exacerbation period - Kurnosova N.V.; Kuzmenko A.V.; Kuzmenko V.V. (Саратовский научно-медицинский журнал, 2010)
60 women were examined with the diagnosis of chronic cystitis in exacerbation period. Cystoscopy with biopsy of urinary bladder mucous was made on the first day and the tenth day. The patients were examined by means of the battery of psychometric and psychological methods. Women were divided into two equal groups. The first group took Furamag, the second group - Furamag and Adaptol. The patients complained of dysuria on the first day There was moderate leukocyturia in the urinalysis. Intensive leukocytic infiltration was determined in the biopsy of urinary bladder mucous. In assessing psychic status in patients, the tendency to social isolation was determined in both groups for the first day Laboratory findings were normalized on the tenth day; the dysuria was cropped in both groups in 100 %. Leukocytic infiltration in the biopsy of urinary bladder mucous was changed by lymphocytic one, and proliferative processes were increased. In the second group of patients more rapid relief of anxiety and depressive disorders was noted